STUDI POTENSI JENIS TUMBUHAN BAWAH DAN EPIFIT SEBAGAI TANAMAN HIAS PADA KAWASAN PPTAT YAYASAN DIAN TAMA KALIMANTAN BARAT - Ilhamullah, Bakti; Ekyastuti, Wiwik; Husni, Harnani (JURNAL HUTAN LESTARI, 2015)
West Kalimantan is one of the centers of biodiversity. It’s has a wealth of flora are very much and most potential as an ornamental plant. Yayasan Dian Tama in Toho Ilir very support educational activities, research and ecotourism. This study aims to determine the potential down and epiphytes plant species as ornamental plants are contained in secondary forest area PPTAT Yayasan Dian Tama Toho Ilir. The research time is two week effectively in the field from September 1 until 2014 September 14. This research is using a single plot with a plot size of 20m x 50m (0.1 Ha), as many as eight plots and the total number of observations made plot is 0.8 hectares. The results found that 15 plant species very potential as an ornamental plant, namely: Aglaonema crispum, Aglaonema nitidum, Aglaonema simplex, Asplenium nidus, Bauhinia sp., Bulboppylum sp., Chrysalidocarpus sp., Cordyline fruticosa, Drynaria sparsisora, Globba sp., Hemamolena sp., Lygodium circinnatum, Lygodium scandens, Molineria latifoliadan Nephrolepis sp. From the 15 species of cover coops and epiphytes as a ornamental plant, that are Nephrolepis sp. with a density 68.74 clumps / ha, Aglaonema nitidum with a density of 47.5 clumps / ha and Hemamolena sp. with a density of 42.5 clumps / ha. As for the highest frequency is the type of Aglaonema nitidum, Aglaonema simplex and chrysalidocarpus sp. each with a value of F = 0.5. Keywords : Ornamental plant, Epiphytes, potential, research.